Study of parallel operation single phase H-bridge CSI and H-bridge VSI - Suroso, Suroso; Winasis, Winasis; Supriyanti, Retno (Institute of Advanced Engineering and Science, 2025)
In some applications, parallel operation of some single-phase inverters with different characteristics is a necessity, such as in a photovoltaic power conversion system. Each power inverter with its power source works, delivering power to a common load which cannot be supplied by a single power inverter. This paper proposed a novel parallel operation of two different power inverter circuit types. H-bridge voltage source inverter (HB VSI) and H-bridge current source inverter (HB-CSI), supplying AC power to a common load. The proposed inverter system was examined and its operation characteristics were analyzed using computer simulation. Moreover, a laboratory prototype of the inverter system was made and examined to validate some principal characteristics of the inverter system experimentally. Test results showed that by combining the HB-VSI and HB CSI, a lower distortion of load current was achieved, specifically, total harmonic distortion (THD) of Iload was less than 1%. This phenomenon happens even the THD of AC currents generated by HB-VSI and HB-CSI at 6.95% and 6.18%, respectively.